Rural and Small Town Residents and the Rural Mystique: Data from Texas. (29th August 2018) - Theodori, Gene L.; Willits, Fern K.
Abstract: This study used data from a 2012 survey of persons living in small and rural places in Texas to assess their views concerning selected positive and negative descriptions of rural and urban life. Findings suggest that ruraland small town Texans tended to accept positive images of rural life, toreject negative views of rurality, and to be somewhat ambivalent with respect to urban living. Bivariate and multiple correlation and regression analyses found relationships between subjects' selected sociodemographic characteristics and their views related to rural and urban life. The article presents comparisons of these findings with the results of previous research on the rural mystique and advances suggestions for additional exploration of these ideas.